(untitled) (Journal of the College of Basic Education, 2023)
The virtuous Dr. Salih Ahmed Al-Fahdawi, Head of the Musical Arts Department at the College of Music, asked me toFine Arts - University of Baghdad I wish to participate in the eighth scientific conference of the college.Due to the short period of time, I collected my thoughts and chose to write about an Iraqi artist.The Forgotten One who gave a lot to the musical and lyrical heritage of Baghdadi, and he is the artist SalihThe Kuwaiti, and his most prominent role in the music and singing of Al-Baghdadi, and I hope that I have succeeded in choosingthis topic.From the researcher’s point of view, the Kuwaiti artist Saleh is one of the pioneers of musicians and composers.Prominent Iraqis who left their artistic imprints on the course of the Iraqi art movement since the earlyThe twentieth century until the year 1951 AD, when his works were dispersed and almost disappeared. Therefore, this researchIt is a serious attempt to study the life of this forgotten artist and his productions.The research consists of four chapters. In the first chapter, the researcher deals with the research methodology.and previous studies. In the second chapter, the researcher dealt with the life and art of Saleh Al-Kuwaiti.The third chapter of the research dealt with the researcher, Saleh Al-Kuwaiti, and his impact on the artistic movement.Iraqi. Finally, the researcher concluded the fourth chapter with conclusions and recommendations as well as the sources.And the scientific references that the researcher relied on, and one appendix that the researcher quoted due to its necessity fromThe eighth part of the book (History of the Iraqi Ministries) by the late Iraqi historian Mr. Abdel RazekAl-Hasani is in its seventh, expanded and expanded edition, published by the General Cultural Affairs House.The researcher hopes that the best participants in this conference will express their opinions and observations.And their suggestions on the subject of the research are a service to the artistic procession in our dear Iraq, and from the dear God.The Almighty We draw determination and success.